Prognostic factors of colorectal cancer patients with brain metastases. (May 2021) - Roussille, Pauline; Auvray, Marie; Vansteene, Damien; Lecomte, Thierry; Rigault, Eugénie; Maillet, Marianne; Locher, Christophe; Dior, Marie; Hautefeuille, Vincent; Artru, Pascal; Mabro, May; Touchefeu, Yann; et al.
Highlights: ECOG performance status 0 or 1 is the best prognostic factor. Single BM and less than 3 chemotherapy lines are also good prognostic factors. GI-GPA and DS-GPA are relevant scores for brain metastases from colorectal cancer. Abstract: Introduction: Brain metastases (BMs) from colorectal cancer (CRC) are rare (≈2%) but are increasing with the improvement of CRC prognosis. The main objective of this study was to evaluate the prognostic factors of BM from CRC. Materials and methods: This multicenter retrospective study included all consecutive patients with BM from CRC diagnosed between 2000 and 2017. Theory/calculation: Prognostic factors of OS were evaluated in univariate (log-rank test) and multivariate analyses (Cox regression model). These prognostic factors could help the management of patients with BM from CRC. Results: A total of 358 patients were included with a median age of 65.5 years. Primary tumors were mostly located in the rectum (42.4%) or left colon (37.2%) and frequently KRAS -mutated (56.9%). The median time from metastatic CRC diagnosis to BM diagnosis was 18.5 ± 2.5 months. BMs were predominantly single (56.9%) and only supratentorial (54.4%). BM resection was performed in 33.0% of the cases and 73.2% of patients had brain radiotherapy alone or after surgery. Median OS was 5.1 ± 0.3 months. In multivariate analysis, age under 65 years, ECOG performance status 0–1, single BM and less than 3 chemotherapy lines before BM diagnosis were associated with better OS. Prognostic scores, i.e. recursive partitioning analysis (RPA), Graded Prognostic Assessment (GPA), Disease Specific-Graded Prognostic Assessment (DS-GPA), Gastro-Intestinal-Graded Prognostic Assessment (GI-GPA) and the nomogram were statistically significantly associated with OS but the most relevant prognosis criteria seemed the ECOG performance status 0–1. Conclusions: ECOG performance status, number of BM and number of chemotherapy lines are the most relevant factors in the management of patients with BM from CRC.